HUMBLEBRAG OF RURAL YOUTH: REORIENTATION OF YOUTH TOWARDS TECHNOLOGY AND ITS IMPACT ON FAMILY RESILIENCE - Imron, Ali; Marzuqi, Muhammad Ilyas; Pradana, Galih Wahyu (Universitas Airlangga, 2024)
Internet usage in the current digital era has become increasingly pervasive, with teenagers emerging as the largest demographic of users. A specific tendency among teenagers to heavily rely on gadgets (gawais) or social media is called humblebrag. The condition of humblebrag is a symptom that is worrying for families because adolescents become less concerned about their families, so it has an impact on family resilience. This study aims to describe the reorientation of rural youth toward technology and its effects on family resilience. A qualitative research method was employed in Delegan Village, Panceng District, Gresik Regency. The research subjects included teenagers exhibiting humblebrag tendencies, their parents, and community leaders, selected through purposive sampling. Data collected involved observations, in-depth interviews, and literature studies. The data were analyzed using the interactive Miles and Huberman technique. The reorientation of rural youth towards technology (gawai) started due to the influence of their peers, especially the demand for online learning due to the pandemic. Insufficient parental supervision has led to excessive gadget use. This condition is caused by dysfunction in the family. The reorientation of rural youth towards technology has a major impact on family resilience, including legality and family integrity, physically, economically, psychologically, and socio-culturally. The role of parents is essential to monitor the behavior of teenagers towards the use of gawais. In addition, fulfilling the love of both parents is the main solution to realizing changes in the child's condition.